The frequency of clinical and subclinical hypothyroidism in transfusion dependent thalassemia patients in Slemani city /Iraq - Dezheen Jamal Mohammed Rashid; Kawa Muhamad Ameen; Nawsherwan Sadiq Mohammed (Advanced Medical Journal)
Background and objective: Thyroid disorders caused by blood transfusion in thalassemia patients could affect human health and growth, this study was conducted to determine the frequency of clinical and subclinical hypothyroidism in blood transfusion-dependent thalassemia patients in the city of Slemani, Kurdistan Region, Iraq.